The Role of Management Accountants in the Vuca Era - Syamsuddin; Sri Mutiah Husaini; Nur Azizah Afifah Idrus; Sri Sundari (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article aims to present a literature review discussing the role of management accountants in the VUCA era and how they adapt to rapidly changing and unpredictable conditions. The management accounting profession faces numerous challenges in this era, requiring effective strategies to address them while adhering to professional ethical codes. The analysis conducted based on relevant literature indicates that management accountants are expected to be responsive to technological changes by developing digital technology skills.